Relationship of participation in specific sports to academic performance in adolescents: A 2-year longitudinal study - Ishihara, T.; Nakajima, T.; Yamatsu, K.; Okita, K.; Sagawa, M.; Morita, N. (Scandinavian Journal of Medicine & Science in Sports, 2020)
Physical activity is considered a promising behavior to improve cognitive function and academic performance in adolescents. As evidence on the relationship of specific sports activity is not conclusive, this study aimed to determine the longitudinal relationships of different sports to academic performance in adolescents and evaluate the cardiorespiratory fitness mediation effect of these sports. We focused on the demands of complex motor skills and the differences between individual sports versus team sports. Four hundred and sixty-three 7th-grade students (227 girls and 236 boys) were followed-up over 2 years. Data regarding participation in sports activities, types of sports activities, academic performance, and cardiorespiratory fitness were obtained at baseline and after a 2-year follow-up. Structural equation modelling revealed that participation in all sports activity was positively associated with improvement of academic performance from baseline to follow-up, and that these associations were mediated by cardiorespiratory fitness gains. Participation in sports activities that require more complex motor skills and individual sports activity was directly associated with an improvement of academic performance from baseline to follow-up. Furthermore, quitting sports activities was negatively associated with academic performance via a reversal in cardiorespiratory fitness gains. These findings indicate that participation in specific sports may have significant benefits for academic performance in adolescents. Although these relationships are presumably mediated by cardiorespiratory fitness, sports activities that require more complex motor skills and individual sports participation may be directly related to academic performance. Considering that quitting sports activities reversed these benefits, sustained participation in sports is important for academic success.